2014
DOI: 10.20510/ukjpb/2/i1/91143
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal Plants Used in Liver Protection - A Review

Abstract: Liver is the very important part of our body responsible for the maximum metabolic and secretory activities and therefore appears to be a sensitive target site for substances modulating biotransformation. Liver is also associated in detoxification from the exogenous and endogenous challenges like xenobiotics, drugs, viral infections and chronic alcoholism. The period and intensity of the pharmacological response to drugs is influenced by their metabolic rate and hence substances capable to modify drug metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Different medicinal herbs and plants extracts have potent hepatoprotective activity in various animal models [8,1]. Nigella sativa, a dicotyledon of the Ranunculaceae family, contains major phenolic compounds such as thymoquinone, dithymoquinone, thymohydroquinone, and thymol [9].…”
Section: Introductionmentioning
confidence: 99%
“…Different medicinal herbs and plants extracts have potent hepatoprotective activity in various animal models [8,1]. Nigella sativa, a dicotyledon of the Ranunculaceae family, contains major phenolic compounds such as thymoquinone, dithymoquinone, thymohydroquinone, and thymol [9].…”
Section: Introductionmentioning
confidence: 99%
“…The phytochemical screening realized on Dichrostachys cinerea leaves has showed the presence of polyphenols, flavonoids and tannins [14][15][16][17][18][19][20][21][22][23][24][25][26] . These results are in line of others studies which already shown the presence of polyphenols, flavonoids and tannins in extract of leaves of Dichrostachys cinerea 27 .…”
Section: Discussionmentioning
confidence: 99%
“…14 In the present situation, there is an enhanced tendency to discover antioxidants from natural sources as most of the currently available drugs for the treatment of hepatic illnesses are inadequate and have been associated with severe adverse reactions. [14][15][16][17][18][19] Despite that there have been lots of plant-based medicines used to treat liver ailments, 19 such medicines were not scientifically characterized even in pre-clinical studies using animal models. Rumex abyssinicus Jacq.…”
Section: Introductionmentioning
confidence: 99%